IMPACT OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) ON WRITING SKILLS OF ESL LEARNERS AT SECONDARY LEVEL - Dr. Fatima Zafar Baig, Muhammad Zahid Bashir, Aqsa Javaid, Zafar Iqbal (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The new and emerging information and communication technology (ICT) in twenty-first century turned the attention of ESL practitioners from the conventional and teacher-centered pedagogy to more learner-oriented methods. The initiation of ICT has made tremendous changes in the present-day world. The current study aims to investigate the impact of ICT on the writing skills of ESL learners at secondary level. For this purpose, the students of secondary schools in District Vehari were taken as respondents. Cluster sampling technique has been employed to get the required sample. It is an experimental research, so controlled group and experimental group were made, each having 25 students. A pre-test has been conducted that was comprised of an essay type question and the students were asked to write an essay on the given topic. The results of Pre-test were documented. The experimental group was given a treatment for 15 days. They were taught English with the help of ICT in computer lab. After the treatment of 15 days a post-test has been conducted for both groups on the same pattern. The test has been marked according to the same rubric. The results of the pre-test and post-test for the controlled group and experimental group have been analyzed. The difference between the scores of the students in their pre-test and post-test explicitly designates positive and productive role of ICT in English language teaching. The results indicates that ICT plays a significant role in enhancing the writing skills of ESL learners